Pengaruh Kompres Hangat Pada Abdomen Terhadap Nyeri Desmenore Pada Mahasiswi Kebidanan Politeknik Bhakti Asih Purwakarta Tahun 2024 - Yulianti, Lia (CV. Green Publisher Indonesia, 2025)
Dysmenorrhea is one of the most common complaints experienced by adolescent girls and women of reproductive age during menstruation, which can interfere with daily activities and quality of life. One non-pharmacological method that can be used to reduce dysmenorrhea pain is warm compress therapy. This study aims to determine the effect of warm abdominal compresses on reducing dysmenorrhea pain among midwifery students at Politeknik Bhakti Asih Purwakarta. This research used a quasi-experimental design with a one group pretest-posttest approach. A total of 36 respondents were selected using purposive sampling technique based on specific inclusion and exclusion criteria. Data were collected using a questionnaire and pain observation sheet, then analyzed using statistical tests with SPSS. The results showed a significant reduction in pain levels before and after the warm compress was applied (p < 0.05). Therefore, it can be concluded that warm abdominal compresses are effective in reducing dysmenorrhea pain and can be considered a safe and practical non-pharmacological therapy alternative for young women.